2006
DOI: 10.1007/s11661-006-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

A study of nonisothermal austenite formation and decomposition in Fe-C-Mn alloys

Abstract: Experiments using ahot-stage confocal scanning laser microscope (CSLM) havebeen carried out to observe phase transformations in two steels: Si-killedr esulfurized Fe-0.38w tp ct C-1.43 wt pct Mn and Al-killed Fe-0.20 wt pct C-0.87 wt pct Mn. Austenite formation during continuous heating was investigated on the surface of samples that were etched to reveal the ferrite and pearlite regions. It was found that the austenite precipitated first at the pearlite coloniesa nd subsequently in the ferrite phase. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
(24 reference statements)
2
23
0
Order By: Relevance
“…The initial microstructure has an impact on the kinetics of austenite formation, as pointed out in earlier works [11][12][13]. Experimental studies [14,15] of the anisothermal formation of austenite in ferrite-pearlite aggregates revealed different kinetics of the γ/α interface migration towards pearlite, in comparison to its advance into proeutectoid ferrite. Dilatometric data [16] are in agreement with the different kinetics of austenite growth in pearlite and proeutectoid ferrite.…”
Section: Introductionmentioning
confidence: 67%
“…The initial microstructure has an impact on the kinetics of austenite formation, as pointed out in earlier works [11][12][13]. Experimental studies [14,15] of the anisothermal formation of austenite in ferrite-pearlite aggregates revealed different kinetics of the γ/α interface migration towards pearlite, in comparison to its advance into proeutectoid ferrite. Dilatometric data [16] are in agreement with the different kinetics of austenite growth in pearlite and proeutectoid ferrite.…”
Section: Introductionmentioning
confidence: 67%
“…The change in transformation mode from diffusion controlled to massive was observed by Schmidt et al, [26,27] who studied the austenite formation from ferrite-pearlite microstructure during continuous heating using hot-stage confocal microscopy. During the experiments, under conditions above the T 0 temperature, the growth rate increased drastically and it was claimed that the interface-reaction-controlled growth mechanism was responsible for the transformation.…”
Section: Growth Types Of Individual Grainsmentioning
confidence: 81%
“…The relationship between these two processes generally means that the faster the migration rate of the interface, the less likely it is to be smoothed out before it can be observed. In previous studies of CSLM observations, interface migration has been observed for a range of transformations in steels: Widmanstätten ferrite precipitation 4,5) ; austenite to d-ferrite transformation, 1,6) austenite to pearlite 4) and ferrite plus pearlite to austenite. 5) In many of these cases, the surface structure is not preserved after the transformation, due to either rapid surface diffusion and high temperatures or sub- Table 2(b).…”
Section: High Temperature Confocal Scanning Laser Microscopymentioning
confidence: 89%
“…Significant improvement to current understanding of austenite formation is possible using in situ observational techniques [1][2][3] to study the behavior of migrating interfaces, in terms of rate, evolving morphology, and effect of initial structure, during the phase change. One of these techniques, more recently developed by Emi 2) for high temperature observation of metals, is the hot stage Confocal Scanning Laser Microscope, [4][5][6][7] (CSLM), which will be utilized in the current investigation.…”
Section: Introductionmentioning
confidence: 99%